Kinetics of CO2 absorption by aqueous N, N-diethylethanolamine solutions: Literature review, experimental results and modelling. (4th May 2015) - Monteiro, Juliana G.M.-S.; Knuutila, Hanna; Penders-van Elk, Nathalie J.M.C.; Versteeg, Geert; Svendsen, Hallvard F.
Abstract: This work studies the kinetics of CO2 absorption into N, N-diethylethanolamine (DEEA) solutions. A comprehensive literature review is presented, in an attempt to understand the reasons behind the scatter observed in the literature data. Experiments were performed to measure the physical solubility of N2 O in aqueous DEEA solutions in a concentration and temperature range that encloses the kinetics data range. Additionally, new data on mass transfer and kinetics of CO2 into aqueous DEEA solutions were produced in a stirred cell reactor. The data show an unexpected behaviour from 3 M DEEA and up, which is not explained by taking the system non-idealities into consideration and revaluating the kinetics using activity basis. A DEEA clustering hypothesis is proposed to explain such behaviour. It is shown that the clustering hypothesis is compatible with the thermodynamic properties of aqueous DEEA solutions, and can be used to qualitatively explain the solubility and kinetics data presented in this work. Highlights: There is a scatter in studies on the kinetics of CO2 absorption into DEEA solutions. New kinetics data show an unexpected behaviour from 3 M DEEA and up. The DEEA clustering hypothesis is proposed to explain such behaviour. The clustering hypothesis qualitatively explains the new solubility and kinetics data. The clustering hypothesis matches the thermodynamic properties of DEEA solutions.